Synthesis of a Cellulose-based Highly Cross-linked Adsorption Resin and its Mechanism for Phenol Adsorption - Yiyu WANG; Jingdong LIANG; Yunwei ZHANG; Jinyu TAN; Qingli HU; Yan ZHANG (Kuangchan zonghe liyong)
With cellulose and styrene as raw materials, cellulose grafted styrene hypercross-linked polymer adsorption resin (CGS-HCP) was prepared by the grafting polymerization-diplomatic coupling two-step method. The pore structure and surface chemical properties of the materials before and after preparation were analyzed by BET, XPS, FTIR, SEM and other characterization methods. In addition, the adsorption performance of CGS-HCP for phenol was investigated. The results show that the prepared CGS-HCP has abundant micropores and mesopores, with an average pore size of 3.38 nm and a specific surface area of 525.06 m2/g. Compared with the original cellulose powder CGS-HCP, a large number of benzene ring groups and oxygen-containing functional groups were introduced to further enhance the adsorption of phenol by CGS-HCP. The kinetic and thermodynamic analysis of the phenol adsorption experiment showed that the adsorption process was spontaneous, exothermic and entropy reduction. The maximum adsorption capacity of CGS-HCP for phenol reached 29.438 mg/g, which proved that CGS-HCP had a good removal effect on phenol. The large number of meso-microporous structures inside the resin and the memory groups on the surface of the resin was the main reasons for the strong adsorption.